PENILAIAN TAMU TERHADAP KUALITAS PELAYANAN HOMESTAY DI DESA WISATA BUKIT BATU KABUPATEN BENGKALIS - Valenzia, Angela Rivera; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tourism in Indonesia presents immense opportunities and potential, serving as a major driver for economic development in many regions. One of the locations with significant tourism potential is Bukit Batu Tourism Village, situated in Bukit Batu Subdistrict, Bengkalis Regency. This study focuses on guest evaluations of the service quality of homestays in Bukit Batu Tourism Village. The primary objective is to assess guest satisfaction levels with the services provided by homestays in the village. The research adopts a quantitative method with a descriptive approach, collecting data through surveys of guests who stayed at homestays in the tourism village. The survey utilized a questionnaire based on dimensions of service quality, including tangibles, empathy, responsiveness, reliability, and assurance. The findings reveal that service quality plays a critical role in creating positive impressions among guests and must be continuously improved to meet their expectations. One key aspect highlighted is the importance of ensuring uniformity in service delivery across all homestays. Given that guests are highly attentive to every detail of the service, clear standardization is essential to ensure that all homestays provide consistently high-quality experiences. Keywords: Guest Evaluation, Service Quality, Homestay, Tourism Village